2007
DOI: 10.1038/sj.ijir.3901537
|View full text |Cite
|
Sign up to set email alerts
|

Monthly income, standard of living and erectile function in late life

Abstract: This was a cross-sectional study that enrolled 160 men aged 50 and above who were sexually active (sexual intercourse in the preceding 6 months) from a large primary care treatment centre. The subjects of interest were elderly aged 65 and above, and men aged 50-65 were used for comparison. The overall response rate was 66.9%. The men who participated were generally more affluent. Standard of living was measured by the presence of maid and housing type. Erectile function (EF) score was significantly higher in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…drugs abuse), and standard of living. Indeed, although only a few population‐based ED studies have included income in their analyses, most found significant associations between income‐derived standard of living and men's sexual health (Cheng et al ., ). However, we decided not to include this variable because of the low response rate we usually obtain on income questions in real‐life clinical practice during standard office visits.…”
Section: Discussionmentioning
confidence: 97%
“…drugs abuse), and standard of living. Indeed, although only a few population‐based ED studies have included income in their analyses, most found significant associations between income‐derived standard of living and men's sexual health (Cheng et al ., ). However, we decided not to include this variable because of the low response rate we usually obtain on income questions in real‐life clinical practice during standard office visits.…”
Section: Discussionmentioning
confidence: 97%
“…For a more complete picture of factors related to educational status, the current analysis also could have included patients' monthly income, socioeconomic well-being, and standard of living. Indeed, although only a few population-based ED studies included income as part of their analyses, most of them found significant associations between income-derived standard of living and men's sexual health [38]. Because educational status is not necessarily related with monthly income, it would be interesting to examine the potential correlation between the two to address both DSH and compliance with PDE5s in this context.…”
Section: Discussionmentioning
confidence: 99%
“…To create a more complete picture of factors related to low response rate, the current analysis also could have included patients' monthly income, their socioeconomic well‐being, and their standard of living. Indeed, although only a few population‐based studies included income as part of their analyses, most of them found significant associations between income‐derived standard of living and men's sexual health [43,44]. This could be even more interesting among PCa patients, as it was demonstrated that low‐income partnered patients had better mental health, less urinary bother, higher spirituality, and lower symptom distress than unpartnered participants.…”
Section: Discussionmentioning
confidence: 99%